53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-1534
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Shooting Shadowing for Sensitivity Analysis of Chaotic Systems and Turbulent fluid flows

Abstract: Sensitivity analysis methods are important tools for research and design with simulations. Many important simulations exhibit chaotic dynamics, including scale-resolving turbulent fluid flow simulations. Unfortunately , conventional sensitivity analysis methods are unable to compute useful gradient information for long-time-averaged quantities in chaotic dynamical systems. Sensitivity analysis with least squares shadowing (LSS) can compute useful gradient information for a number of chaotic systems, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Equation (5b) enforces the continuity of v across consecutive segments, Equation (5c) is the linearized version of Equation (1) around s, and Equation (5d) enforces the direction v to be normal to f. Finally, η is a time-dilation term between the reference and the shadowing trajectory. We briefly describe the solution of the minimization problem in Equation 5, and more details can be found in Reference [21,22]. We reformulate Equation 5as…”
Section: Sensitivity Analysis Of Chaotic Systems Using Mssmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (5b) enforces the continuity of v across consecutive segments, Equation (5c) is the linearized version of Equation (1) around s, and Equation (5d) enforces the direction v to be normal to f. Finally, η is a time-dilation term between the reference and the shadowing trajectory. We briefly describe the solution of the minimization problem in Equation 5, and more details can be found in Reference [21,22]. We reformulate Equation 5as…”
Section: Sensitivity Analysis Of Chaotic Systems Using Mssmentioning
confidence: 99%
“…Although computationally expensive, the method can give values for the sensitivities of time-averaged quantities that match well with finite differences. In this work, the preconditioned Multiple-Shooting (MSS) [21,22], a computationally more efficient version of the LSS, is used to evaluate sensitivities of time-averages.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the cost of the two main adjoint-based sensitivity methods in the literature, namely the Least Squares Shadowing (LSS) 26 and the Ensemble Adjoint (EA) methods, increases with the number and/or magnitude of positive Lyapunov exponents in the discrete system. The computational cost of shadowing-based approaches, including the original LSS method, the Multiple Shooting Shadowing (MSS) method 2 and the Non-Intrusive LSS (NILSS) method, 3,17 is proportional to the number of positive Lyapunov exponents. Under optimistic assumptions, including uniform hyperbolicity and exponential decay of correlations, Chandramoorthy et al 5,6 showed that the mean squared error in the EA estimator is a power law of the computational cost, where the power constant depends on the leading exponent.…”
Section: Application To Chaotic Adjointsmentioning
confidence: 99%